Optical detection system for free fatty acids in crude palm oil based on N-bromosuccinamide catalyst - Che Sulaman, Norsyamimi (2019)
Free fatty acids (FFAs) content in crude palm oil (CPO) is one of parameter that dictated the price of palm oil product. In this study, an alternative optical technique system on detection of FFAs in CPO based on chemical pathway using base catalyst was investigated in order to enhance the current method that practices in industrial with more advantageous in term of using time saving, greener practices and environmentally friendly. FFAs in CPO involved a direct conversion of FFA to form fatty hydroxamic acid (FHA) with hydroxylamine in order to increase its detection prior to coloured metal complexes formation. Coloured metal complexes are an indicator in optical detection using UV-Visible (UV-Vis) spectrophotometer analysis. However, the colour changes of the FHA- V(V) complexation was observe by naked eye before characterize using the UV- Vis spectrophotometer for intensity of the complex. Before this, there was no previous study that study the detection of the FFA in CPO via chemical pathway. A rapid response time of 5 min reaction with one third of mass reactant reduce from initial mass was achieved in conversion of FFAs to FHAs in presence of N- Bromosuccinamide (NBS) as base catalyst and Vanadium (V) (V(V)) as metal ion were used. The reaction was carried out under optimize temperature at 70 °C and 150 rpm shaking. The absorptivity of FHA complexes was detected at 430 nm (range 420 nm to 440 nm) using UV-Vis spectrophotometer. From studies, it can be concluded that detection of the FFA in CPO was successful. The result from develop method was validated with standard titration method by Malaysian Palm Oil Board (MPOB) using spiked CPO sample. Optimization studies were investigated in order to achieve an optimum condition for each parameter for best monitoring system. A linear calibration plot correlation coefficients (R²) is 0.9902 which able to detect down to 0.7813 % of FFA in CPO. A good correlation was obtained between proposed method and MPOB standard titration method (R=0.9157). Paired t-test was used to determine the significant difference between these two methods. According to paired t-test calculation, there is no significant difference between these two methods at 95% confident level (calculated t=1.099, tabulated t=2.776).